2015
DOI: 10.3390/ijms161125989
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Human Adipose Tissue Mesenchymal Stem Cells on the Regeneration of Ovine Articular Cartilage

Abstract: Cell therapy is a promising approach to improve cartilage healing. Adipose tissue is an abundant and readily accessible cell source. Previous studies have demonstrated good cartilage repair results with adipose tissue mesenchymal stem cells in small animal experiments. This study aimed to examine these cells in a large animal model. Thirty knees of adult sheep were randomly allocated to three treatment groups: CELLS (scaffold seeded with human adipose tissue mesenchymal stem cells), SCAFFOLD (scaffold without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 55 publications
0
24
0
1
Order By: Relevance
“…E : Histological evaluation of the newly formed cartilage. Reproduced with permission of Yan et al (), Hao et al (), Park et al (), and Courtesy of Zorzi et al ().…”
Section: Current Management Of Oamentioning
confidence: 99%
See 1 more Smart Citation
“…E : Histological evaluation of the newly formed cartilage. Reproduced with permission of Yan et al (), Hao et al (), Park et al (), and Courtesy of Zorzi et al ().…”
Section: Current Management Of Oamentioning
confidence: 99%
“…The combination of ADSCs not only with growth factors, but also with different materials, for example, silk fibroin (Correia et al, ; Ding et al, ), collagen (Masuoka et al, ), gelatin (Dang et al, ), alginate, and agarose scaffolds (Awad et al, ), which provide the cells with 3D environment, showed to facilitate their chondrocytic differentiation too. Nevertheless, Zorzi et al () managed to achieve efficient repair of AC defect in ovine models by only ADSCs, and even showed higher ICRS scores as compared to their scaffold combined application. Besides BMSCs and ADSCs, there are further MSCs with chondrogenic potential, such as muscle, synovium, and periosteum derived MSCs.…”
Section: Advanced Therapiesmentioning
confidence: 99%
“…Numerous studies on the repair of osteochondral ailments using MSCs have been conducted in sheep. Most of the studies (listed in Table 1) have reported the usefulness of MSCs for improving the condition of joint ailments compared to that of the control (Guo et al 2004;Feitosa et al 2010;Zscharnack et al 2010;Al Faqeh et al 2012;Caminal, Fonseca, et al 2014;Song et al 2014;Garcia et al 2014;Zorzi et al 2015;Desando et al 2016;Whitehouse et al 2017;Abdalmula et al 2017;Feng et al 2018). In addition to cultured MSCs, the BM aspirate too has been reported to improve cartilage healing (Duygulu et al 2012).…”
Section: Msc Studies In Sheepmentioning
confidence: 99%
“…It has been reported that, apart from the autologous or allogeneic MSCs, xenogenic AD-MSCs loaded onto the chitosan/collagen scaffold also promote cartilage healing. A higher International Cartilage Repair Society Score (ICRS-1) in animals treated with the cells compared to those of the scaffoldimplanted or control animals was reported (Zorzi et al 2015). Contrary to the above studies, one of the sheep experimental studies has failed to give any positive outcome for the OA conditions compared to the control upon intra-articular implantation of the autologous MSCs.…”
Section: Msc Studies In Sheepmentioning
confidence: 99%
“…[35][36][37][38] The concept was successfully tested in a large animal model. 39 However, after a consultation to the Brazilian regulatory agency (ANVISA), it was requested that, before the locally produced membrane-assisted chondrocyte could be available for a larger scale clinical use, its safety and feasibility be tested.…”
mentioning
confidence: 99%